Cultural Maintenance in the Face of Language Shift- Young Sindhi Muslims in Karachi, Pakistan - Muhammad Hassan Abbasi (University of Chitral Journal of Linguistics and Literature, 2021)
The Sindhi language, a descendent of a pre-Vedic Prakit language is the most widely spoken language in South-Asia. Sindhi speech community comprises of both Muslims, and Hindus which have distinct cultural and religious practices, yet they are socially connected because of the geographical link with their land. However, due to the partitioning of the Indian sub-continent many Sindhi Hindus migrated to India, Malaysia, Singapore, Indonesia, United Kingdom, Hong Kong, and many other countries. There has not only been external diaspora but within Pakistan there has also been internal diaspora of younger Sindhi Muslims who have moved to cities like Karachi, Hyderabad, and Sukkur to pursue tertiary education. These young speakers have acquired and learnt the dominant languages Urdu and English as their second and third languages while shifting away from their native Sindhi language. This study investigates the identity markers which have enabled them to retain their Sindhiness[1]. Semi-structured interviews were conducted with 20 male and female young Sindhis and shadow observation of three participants in Karachi. The analysis shows that young Sindhi speakers have a high sense of group solidarity with their community and retain the use of culturally loaded identity markers which include naming patterns, cuisine, dressing, music, customs, rituals, social values, and networking. According to Fishman (1996) there is a deep relationship between language and culture. Despite a shift away from habitual use of the Sindhi language these respondents have maintained their cultural values and norms.